Faktor-Faktor Penyebab Terjadinya Missfile Dokumen Rekam Medis di Ruang Filling Puskesmas Pulo Brayan Medan - Angelia Putriana; Fince Putri Zega (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Good medical record keeping is a successful management of a health service. Filling is part of the Medical Record Unit (URM) which has an important role in functioning for various purposes, protecting the confidentiality of the contents of the Medical Record Document (DRM) from unauthorized parties, and protecting the Medical Record Document (DRM) archive from physical and chemical damage. , and biology. Missfile is a medical record file that is lost and misplaced on the medical record file storage shelf in the filling room. A medical record file is said to be misplaced or missing (Missfile) if the file is needed but on the storage shelf the file is not available or does not exist. The impact of a missfile is that it causes patient service in searching medical records to be delayed. Apart from that, it can also result in duplication of medical record numbers and the contents of medical record documents becoming discontinuous. This type of research is descriptive with a qualitative approach whose data collection methods are observation and interviews. The research results showed that factors causing missfiles include the Human Resources (HR) factor, namely the number of medical record officers, only two people who have a high workload, the method factor, namely the absence of SOPs regarding borrowing and returning medical record documents, the machine factor, namely slow shelves. storage of medical record documents and the money factor, namely there is no special budget for the medical record room.